Rationality and Religiosity of Islamic Economy in Facing Global Challenges - Dzarin Gifarian Khaulani; Bening Fathima Rabbaniya Amatillah (UIN Sunan Gunung Djati Bandung, 2023)
Islamic economics actually still has the opportunity to develop and become an alternative in facing global challenges. However, the development of Islamic economics requires a strong theoretical foundation. The purpose of this study is to show the importance of epistemological research in the field of Islamic economics. There are two approaches that can be used in analyzing Islamic economics, namely descriptive and thematic. Both are interrelated in the process of strengthening the study of Islamic economics. Therefore, based on the epistemological approach, there are two types of Islamic economic studies that are normatively based on rationality and religiosity, and both cannot be separated from the moral basis of Islam. This research method uses the literature survey method by utilizing library resources in obtaining data, to prepare a theoretical framework and also to strengthen the methodology. Then the validity of the Islamic economic methodology can be tested based on the consistency of the internal system and its compatibility with various systems that govern the dimensions of human life. By supporting Islamic economics as a normative science, a combination of rationality and religiosity will continue and be sustained, as this will develop an economic flow that is more rooted in global ethics in the future.